(untitled) (REMUNOM, 2025)
The objective of this study was to isolate and select rhizobacteria non-symbiotic diazotrophs capable of solubilizing phosphates and evaluating their efficiency in establishing interaction with corn seedlings (Zea mays L.) in vitro. 57 isolates grew in NFb and JMV culture media, of which 11 showed formations of a transparent halo around the colony cultivated in solid medium added to the NBRIP. The ANOVA detected significance for the parameters: plant height (AP), root length (CR), stem diameter (DC), leaf area (AF), number of leaves (NF) and total dry matter weight (PMST). Regarding FA, all isolates promoted a significant increase compared to the control, with the best results verified for DBSF58, DBSF40 and DBSF20. In the production of PMS mass by seedlings, all isolates differed statistically (p≤0.5) from the control, the highest mean was verified for DBSF40. All isolates selected as diazotrophs showed characteristics for promoting plant growth. Keywords: growth-promoting bactéria; diazotrophs; biological N fixation